A Cry for Help and Protest: Self-Immolation in Young Kurdish Iraqi Women -A Qualitative Study - Pakestan Mohammad Amin; Jila Mirlashari; Alireza Nikbakht Nasrabadi (Shiraz University of Medical Sciences, 2018)
Background: Suicide is a major psychiatric emergency that has always been a topic of great interest to researchers. Self-immolation is a heinous suicide method that is common in Eastern societies. The present study was conducted to explore probable issues which might lead to self-immolation in young Kurdish Iraqi women. Methods: The present qualitative study was conducted in Soran, Erbil Governorate in Iraq, and the surrounding villages of Soran District (March 2015 to May 2016). Using purposive sampling, we conducted 24 in-depth interviews with women who had done self-immolation. The obtained data were analyzed using conventional content analysis. Results: The analysis of the data obtained from the interviews led to the extraction of five categories which seems to be related to self-immolation attempts, including not having control over personal life, marital conflicts, seeking attention, instilling guilt in the family members, and resentment towards male dominant community. Conclusion: Self-immolation is a multidimensional phenomenon that has not come to exist overnight and is rooted in various factors that join to encourage self-immolation attempts by women in critical situations. Comprehensive preventive strategies, such as cultural changes, along with education are required to help lower the rate of self-immolation.